Pó de rocha de basalto como remineralizador de solo - Barros, Gabriela de (2023)
Brazil is one of the largest producers of food and grain in the world and this increase was due to some important factors, including the correction and better use of fertilizers. However, the country is not self-sufficient to meet the demand for fertilizers and the large volume of this input is imported, an alternative is to use waste from mining industries from the exploitation of amethyst quartz in the municipality of Ametista do Sul-Rio Grande do Sul (RS), considering the availability and environmental need for conscious disposal (HARTMANN, 2014) and on the demand for natural fertilizers to agroecological crops and the type of agriculture practiced in the region, where family farming predominates. Therefore, the research project consists of characterizing the physical and chemical composition of basalt, using it as a soil remineralizer. The research project was conducted in a greenhouse, in the experimental field of the Federal University of Santa Maria – UFSM – campus of Frederico Westphalen-RS, the climate is classified as type Cfa, humid subtropical (ALVARES et al., 2013). The soil used in the study was classified as Dystrophic Red Latosol (STRECK et al., 2008), collected in an area of native forest vegetation and seedlings of Cynodon spp. cv. Tifton 85 and the rocks used, are part of the Serra Geral Igneous Province. The samples were collected from residues of an amethyst extraction deposit, carried out in loco unequal and in a random way, later passed through a crusher to be ground. The experiment was arranged in a randomized block design with a total of six treatments and four replications per treatment. Each experimental unit consisted of a plastic vessel of 5 l each, the treatments were doses of rock dust, as follows: T – Control; T1 – 2.0 t. ha-1; T2 – 4.0 t. ha-1; T3 – 8.0 t. ha-1; T4 – 16 t. ha-1; T5 – 32 t. ha-1. The plants underwent 04 cuts of the aerial part and 04 applications of the basalt by-product, with an interval of 28 days between each cut and each application. The soil samples were dried in an oven at 60 degrees, placed in boxes to carry out the following determinations: pH in water, SMP, P, K, Al, Al + H, CTC and Saturation by Base and Al, following methodologies described by (TEDESCO; GIANELLO; BISSANI, 1995). Waste samples underwent the same procedure as soil samples. To determine the size of the particles, they went through the technique of sieving and sedimentation, thus defining the granulometry of the particles by the pipette method (GEE; BAUDER, 1986). The samples of plant material were carried out by sulfuric digestion of the leaf tissue to analyze the levels of macronutrients, according to the methodology described by (TEDESCO; GIANELLO; BISSANI, 1995). The waste used as rock dust from Ametista do Sul-RS presents important chemical elements for the agricultural sector, positively highlighting the environmental, social and economic issue of the Northwest region of RS.